2004
DOI: 10.1172/jci18704
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation end products (RAGE) regulates sepsis but not the adaptive immune response

Abstract: While the initiation of the adaptive and innate immune response is well understood, less is known about cellular mechanisms propagating inflammation. The receptor for advanced glycation end products (RAGE), a transmembrane receptor of the immunoglobulin superfamily, leads to perpetuated cell activation. Using novel animal models with defective or tissue-specific RAGE expression, we show that in these animal models RAGE does not play a role in the adaptive immune response. However, deletion of RAGE provides pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
304
2
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(325 citation statements)
references
References 61 publications
10
304
2
9
Order By: Relevance
“…Rage -/- mice, backcrossed >10 times to a C57Bl/6 background, were generated as described [12] and bred in the animal facility of the Academic Medical Center (Amsterdam, The Netherlands). The Animal Care and Use Committee of the University of Amsterdam approved all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rage -/- mice, backcrossed >10 times to a C57Bl/6 background, were generated as described [12] and bred in the animal facility of the Academic Medical Center (Amsterdam, The Netherlands). The Animal Care and Use Committee of the University of Amsterdam approved all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Several animal studies have shown that RAGE is critically involved in the deleterious effects of acute inflammatory disorders, including sepsis [12,13,14,15,16]. Deletion of the rage gene was initially found to protect against the lethal effects of septic shock in polymicrobial sepsis, which was associated with a strongly reduced activation of NF-κB in the peritoneum and lungs [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the late and progressive stages of AD dysfunction, depletion of the enzyme's chief and essential cofactor, glutathione, reduces overall activity of the GLO1-AGE detoxifying system, thus facilitating increased AGE production and accumulation [65,66]. Altogether, these findings underscore a potentially profound link between peripheral and central inflammation, which prompts the question: to what extent might anti-AGE/RAGE therapies provide protective measures for neurodegeneration and AD, given the prominence of cellular stress driven by increased RAGE ligand burden [67][68][69].…”
Section: Consequences Of Rage Signal Transductionmentioning
confidence: 99%
“…However, controversy arose after a report that Ager deficient mice with EAE displayed no differences in disease severity [67].…”
Section: Rage Snps Animal Findings Human Findingsmentioning
confidence: 99%